STUDY ON BODY COMPOSITION AMONG PHYSICALLY INACTIVE, MODERATELY & HIGHLY ACTIVE COLLEGE TEACHERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Physical activity is any real development including energy use attempted while working, playing, doing family tasks, voyaging, and participating in sporting pursuits by the skeletal muscles of the body. Physical Activity is characterized as anybody development delivered by skeletal muscles that bring about an impressive increment over the resting energy consumption. It alludes to the development of enormous muscle gatherings, as while moving the entire body. It can likewise be characterized as any development between skeletal muscles that applies energy. Physical activity is classified as low, moderate, incredible and strength preparing exercises and should be continuous for in any event 20 minutes. Physical activity's principle attributes are force, term and recurrence and complete physical activity is typically made out of various viewpoints, for example, transport-related, work related, homegrown, and recreation time physical activity, A wide range of physical exercises, or absence of these exercises, have physiological/clinical results.